(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this review was to evaluate the effectiveness of physical therapy interventions reported for use in children with delayed developmental to improve motor skills, cognition, and social skills outcome. PubMed, PEDro, and Google scholar were systematically searched to source for full-text studies published in peer-reviewed journals from 2010 to 2020 for current physical therapy interventions in children with developmental delay. Outcomes were motor skills, social skills, and cognition ability. Results Searches identified 20 randomized trials including 1132 children with developmental delay. Interventions were various with different sample sizes. The most used intervention was dual task with video game/VR, skill instruction and massage therapy. Other interventions such as music therapy, equine, aquatic therapy were also found. Except aquatic therapy, all the interventions type showed to be effective to improve motor, social and cognition in children with DD. Results from this review reveal that dual task with video game/VR and massage therapy are effective to improve motor and cognition and skill instruction, education program including parents is more effective for social skills improvement. The other included interventions showed to be effective, but more evidence is needed.